2012
DOI: 10.1038/jes.2012.63
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of land use on spatial distribution of mortality rates of cancers caused by naturally occurring asbestos

Abstract: This study investigated the spatial distributions of mortality rates of six cancers: mesothelioma, lung cancer, intestinal cancer, nasopharyngeal and laryngeal cancer, liver cancer, and stomach cancer in Dayao using Geographic Information Systems. Relationships between the mortality rates of the six cancers and land use patterns were investigated by Pearson Correlation Coefficients. The results indicated that the mortality rates of nasopharyngeal and laryngeal cancer, lung cancer, intestinal cancer, and mesoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…This finding is consistent with the finding of Wei et al , who found that mortality from cancer may be higher in areas with high proportions of agricultural land or in built-up areas than elsewhere [5]. In this study, land used for industrial plants was classified as built-up land.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with the finding of Wei et al , who found that mortality from cancer may be higher in areas with high proportions of agricultural land or in built-up areas than elsewhere [5]. In this study, land used for industrial plants was classified as built-up land.…”
Section: Discussionsupporting
confidence: 92%
“…The high mortality rates associated with nasopharyngeal, lung, intestinal, and mesothelioma cancers have shown significant associations with two land use types agricultural and urban [5]. Relevant studies have indicated that heavy metal enrichment in soil is associated with human activities, especially in built-up areas and on agricultural land [6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The above considerations are supported by the results of an investigation recently conducted in the Dayao area, China (Wei et al, 2012). The study showed that naturally occurring asbestos may significantly elevate the mortality rates of various malignancies, including nasopharyngeal and laryngeal cancer, intestinal cancer, lung cancer and mesothelioma.…”
Section: Discussionsupporting
confidence: 68%
“…This is not a classic asbestos exposure occupation, so the presumed aetiology was either incidental environmental exposure or idiopathic [11]. Previous autopsy studies have documented metastases in 50% of cases of both pleural and peritoneal mesothelioma, with common sites being the lymph nodes, lung, liver, pleura, bone, adrenal glands and heart [4].…”
Section: Discussionmentioning
confidence: 99%